2022
DOI: 10.21203/rs.3.rs-1683140/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental considerations of acute heat stress assays to quantify coral thermal tolerance

Abstract: Thermal tolerance is variable in corals, yet intrinsic and extrinsic drivers of tolerance are not well understood. Understanding the distribution and abundance of heat tolerant corals across seascapes is imperative for predicting responses to climate change and to support novel management actions. Rapid and high-throughput methods to measure heat-induced coral bleaching sensitivity are increasingly required to understand current and predict future responses to climate change. Experimental evaluations of coral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…At the end of the temperature profiles, corals were maintained at ambient temperature for 11 h prior to physiological measurements. This 11‐h post‐heat stress sampling time point differs from other recent studies that sample immediately after ramping down from heat stress, though it has no effect on measures of photochemical yield (Nielsen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 84%
“…At the end of the temperature profiles, corals were maintained at ambient temperature for 11 h prior to physiological measurements. This 11‐h post‐heat stress sampling time point differs from other recent studies that sample immediately after ramping down from heat stress, though it has no effect on measures of photochemical yield (Nielsen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 84%
“…This may also be due to differences in the timing of measurement between traits as their decline occurs at different rates (Gardner et al, 2017). In A. tenuis, Fv/Fm values were found to be stable 0-24 hours after the end of a similar acute heat stress, while visual pigmentation and chlorophyll decreased up to 24 hours after the end of temperature ramp-down (Nielsen et al, 2022). Therefore delaying the timing of NDVI measurements in our study may have revealed higher divergence in chlorophyll retention between reefs.…”
Section: Divergent Effects Of Acute Heat Stress On Thermal Tolerance ...mentioning
confidence: 99%